THE EFFECT OF GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL COSTS ON FINANCIAL PERFORMANCE WITH CSR DISCLOSURE AS MODERATION - Thioly T. Sitanggang; Fahmi Natigor Nasution; Amlys Syahputra Silalahi (CV. Radja Publika, 2026)
This study aims to analyze the influence of green accounting , environmental performance, and environmental costs on financial performance with Corporate Social Responsibility (CSR) disclosure as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study uses a quantitative approach with a causal research type. The data used are secondary data obtained from annual reports and company sustainability reports. The study population includes 40 companies, with a sample of 26 companies determined through a purposive sampling technique, resulting in 104 panel data observations. Data analysis was performed using panel data regression with the help of EViews software, through the stages of descriptive statistics, classical assumption tests, regression model selection, and hypothesis testing. Based on the results of the study, green accounting and environmental performance have a positive but insignificant effect on financial performance, while environmental costs have a positive and significant effect. In the moderating role, CSR disclosure is unable to strengthen the effect of green accounting , but it is able to strengthen the effect of environmental performance, and weaken the effect of environmental costs on financial performance. These findings indicate that the role of CSR is contextual in moderating the relationship between variables.